A family of Dirichlet Morrey spaces. - Galanopoulos, Petros; Merchán-Álvarez, Noel; Siskakis, Aristomenis G. (Taylor & Francis, 2019)
To each weighted Dirichlet space D_p, 0<p<1, we associate a family of Morrey-type spaces D_{λ,p}, 0<λ<1, constructed by imposing growth conditions on the norm of hyperbolic translates of functions. We indicate some of the properties of these spaces, mention the characterization in terms of boundary values, and study integration and multiplication operators on them.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/5091?template=romeo
Keywords: Medida, Teoría de la; Operadores, Teoría de; Análisis funcional; Dirichlet spaces; Morrey spaces; Carleson measures; Integration operator; Pointwise multipliers